Use of Gamma Radiation Techniques in Peaceful Applications - Almayah, Basim A. (IntechOpen, 2019)
This book deals with gamma radiation in many fields, which encompasses diverse factors that affect human and animal life inside an environment. These fields include nuclear and medical physics, industrial processes, environmental sciences, radiation biology, radiation chemistry, radiotherapy, agriculture and forestry, sterilization, the food industry, and so on. The book covers an overview of gamma background radiations and measurements, radioactive decay, radioecological applications in environmental gamma dosimetry, gamma-ray interaction, monocolor gamma, influence of gamma radiation on dynamical mechanical properties, influence of low-dose gamma irradiation treatments on microbial decontamination, gamma-ray ionization enhancement in tissues, gas-filled surge arresters, modeling plastic deformation located in irradiated materials, radiotherapy, application of radiation and genetic engineering techniques, and gamma-ray measurements using unmanned aerial systems. This book is expected to benefit undergraduate and postgraduate students, researchers, teachers, practitioners, policy makers, and every individual who has a concern for a healthy life.